5
$\begingroup$

Let $X_{n} \in [0,1]$ be adapted to $\mathcal{F}_{n}$ and $\alpha, \beta > 0$ where $\alpha + \beta =1$. Further:

$P(X_{n+1}=\alpha + \beta X_{n} \vert \mathcal{F}_{n})=X_{n}$ or $P(X_{n+1}= \beta X_{n} \vert \mathcal{F}_{n})=1-X_{n}$

Show that $P(\lim\limits_{n\to \infty} X_{n}=0 \operatorname{or} 1)=1$ and if $X_{0}=\theta$ then $P(\lim\limits_{n\to \infty} X_{n}=1)=\theta$

I honestly do not know where to begin:

$E[1_{\{X_{n+1}=\alpha + \beta X_{n}\}} \vert \mathcal{F}_{n}]=X_{n}$

$E[1_{\{X_{n+1}=\beta X_{n}\}} \vert \mathcal{F}_{n}]=1-X_{n}$

Maybe the tower property could help:

$E[E[1_{\{X_{n+1}=\alpha + \beta X_{n}\}}\vert \mathcal{F}_{n+1}] \vert \mathcal{F}_{n}]=X_{n}$

But it leads to nothing.

$\endgroup$
1
  • $\begingroup$ Get rid of the indicator functions and just compute $E[X_{n+1}|F_n]$. $\endgroup$
    – Michael
    Oct 4, 2019 at 22:47

1 Answer 1

6
$\begingroup$
  • Since $(X_n)_{n\geq 0}$ is a bounded martingale, it converges almost surely. Let $X_{\infty}$ denote its a.s-limit. We know that $\mathbb{P}(X_{\infty} \in [0, 1]) = 1$.

  • Now we claim that

    $$ \mathbb{E}[X_{n+1}(1-X_{n+1})] = (1-\alpha^2)\mathbb{E}[X_n(1-X_n)] \tag{1}$$

    holds. Indeed, write $A_{n+1} = \{ X_{n+1} = \alpha + \beta X_n \}$. Then by noting that

    $$ \mathbb{P}(\{ X_{n+1} = \alpha + \beta X_n\} \cup \{ X_{n+1} = \beta X_n\}) \stackrel{\text{(tower)}}{=} \mathbb{E}[X_n + (1-X_n)] = 1, $$

    we may write $ X_{n+1} = \alpha \mathbf{1}_{A_{n+1}} + \beta X_n $. From this, we get

    \begin{align*} \mathbb{E}[X_{n+1}(1-X_{n+1})] &= \mathbb{E}[X_{n+1}] - \mathbb{E}[X_{n+1}^2] \\ &= \mathbb{E}[X_n] - \mathbb{E}[\alpha^2 \mathbf{1}_{A_{n+1}} + 2\alpha\beta X_n \mathbf{1}_{A_{n+1}} + \beta^2 X_n^2] \\ &\stackrel{\text{(tower)}}{=} \mathbb{E}[X_n] - \mathbb{E}[\alpha^2 X_n + 2\alpha\beta X_n^2 + \beta^2 X_n^2] \\ &= (1-\alpha^2)\mathbb{E}[X_n(1-X_n)] \end{align*}

    as desired.

  • From $\text{(1)}$, we get $\mathbb{E}[X_n(1-X_n)] \to 0$ as $n\to\infty$. Then by the dominated convergence theorem,

    $$ \mathbb{E}[X_{\infty}(1-X_{\infty})] = \lim_{n\to\infty} \mathbb{E}[X_n(1-X_n)] = 0. $$

    Since $X_{\infty}(1-X_{\infty}) $ a.s. non-negative, the above computation shows that $X_{\infty}(1-X_{\infty}) = 0$ a.s., and so, we get $\mathbb{P}(X_{\infty} \in \{0, 1\}) = 1$ as desired.

  • Finally, by noting that $X_{\infty}$ is $\{0,1\}$-valued almost surely, we can write

$$ \mathbb{P}(X_{\infty} = 1) = \mathbb{E}[X_{\infty}] = \lim_{n\to\infty} \mathbb{E}[X_n] = \mathbb{E}[X_0] = \theta. $$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.